Brain metastasis or nocardiosis? A case report of central nervous system Nocardiosis with a review of the literature - Hojin Sun; Mariam Goolam Mahomed; Jaimin Patel (Greater Baltimore Medical Center, 2021)
Nocardiosis is an infection caused by the gram-positive bacterium Nocardia, which typically manifests as an isolated pulmonary or systemic disease. Of note, Nocardia has a predilection for the central nervous system (CNS) involvement, which is more commonly seen in systemic nocardiosis rather than as an isolated CNS infection. According to the Centers for Disease Control and Prevention, the estimated incidence of nocardiosis is only 500 to1000 cases in the USA every year, with cases mostly found in immunocompromised people, although infection in the immunocompetent may also occur. Here, we present a case of an immunocompromised patient who presented with neurologic symptoms and intracranial lesions initially concerning metastatic disease. Upon further investigation, the patient was found to have CNS nocardiosis with bacteremia. This is an extremely rare presentation given the lack of concurrent pulmonary and cutaneous involvement. The insidious onset and rarity of nocardiosis can result in a delayed or missed diagnosis. Early recognition is crucial as this is a potentially life-threatening illness. After obtaining adequate culture specimens, empiric treatment must be started expeditiously, keeping in mind the diversity of the Nocardia species and their antimicrobial resistance patterns.